A Female Prehistoric Story: Conceptualization of Time, Environment and Artistic Interpretation - Cabañero Martín, Víctor Manuel (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2022)
This publication aims to present a story for Pre-schoolers and students from the 1st Year of Primary. This story takes as a reference exhibition media from the Segovia Museum, such as replicas from the main panel by Domingo García and the house of the Peña by esteban Vela. Grounded on the location within the exhibition space of both replicas and their integration into a higher space, this story is proposed as an example activity based on the didactic approaches of social sciences. It mostly deals with the conceptualization of time, the immediate space and the interaction of the human being with the environment and it also offers an introduction to the interpretation of prehistoric art.